Implementasi Media Aplikasi Marbel Membaca dalam Mengembangkan Kemampuan Pra Membaca Anak Usia 4–5 Tahun di PAUD Al-Muttaqin: Sebuah Studi Kualitatif - Rohmalia Rohmalia; Siti Kholifah; Muthia Sari; Nuryati Nuryati (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study is motivated to describe the implementation of pre reading skills using the marbel reading application media in 4-5 years old children at PAUD Al-Muttaqin. The method used is qualitative research with a descriptive approach that emphasizes an in-deep understangding of the learning process through the digital application media. Data were collected through observation, interviews with teacher and documentation of learning activities. The results showed that there was an increase in the pre reading ability of early childhood after using the marbel reading application because the us of the marbel application provides effective stimulation in recognizing letters, words and sound in children, thus increasing interest and pre reading ability gradually. In addition, this media makes it easier for teachers to deliver learning materials interactively